REGIONAL FISCAL INDEPENDENCE IN EAST JAVA PROVINCE POST REGIONAL AUTONOMY - Irdam Ahmad (Universitas Islam Indonesia, 2011)
Fiscal dependence has been critized as one of the obstacles in the success of economic development post the regional autonomy. This paper evaluates the level of fiscal independence in districts and cities in East Java Province and the impact of General Allocation Fund and Special Allocation Fund on tax effort of regional government in East Java Province. The result shows that General Allocation Fund significantly affects tax effort, while Special Allocation Fund does not significantly affect tax effort. It also finds that General Allocation Fund influences economic growth, where for one percent increase in General Allocation Fund, regional economic growth increase by 0.28 percent. Keywords: Fiscal independence, general allocation fund, special allocation fund, tax effortJEL classification numbers: H21, H53, H71, H72